2005
DOI: 10.1590/s0103-50532005000800023
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectrometry screening of piperidine alkaloids from Senna spectabilis (Fabaceae) extracts: fast identification of new constituents and co-metabolites

Abstract: O padrão de fragmentação de uma série homóloga de alcalóides piperidínicos isolados de Senna spectabilis foi investigado utilizando-se espectrometria de massas tandem com ionização por electrospray (ESI-EM/EM). A análise dos extratos EtOH e frações das flores e dos frutos de S. spectabilis por ESI-EM e ESI-EM/EM permitiu elucidar a estrutura de quatro componentes pertencentes a uma série homóloga destes alcalóides, bem como de quatro co-metabólitos inéditos. A elucidação estrutural dos co-metabólitos, com base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 30 publications
2
35
0
13
Order By: Relevance
“…88 In addition, the presence of a homologous series of novel piperidine alkaloids has been detected in the fruits of S. spectabilis by means of tandem mass spectrometry with electrospray ionization. 89 A detailed analysis of the structural features of 70 has led to identification of an acetylcholine (ACh) subunit internalized in this (Figure 17), and led to the design of several semi-synthetic derivatives, including (-)-3-O-acetyl-spectaline hydrochloride (73), prepared from 63. This derivative displays cholinergic activity both in vitro and in vivo (IC 50 = 7.32 μM).…”
Section: Brazilian Biodiversity: An Unknown Potential Source For Drugmentioning
confidence: 99%
“…88 In addition, the presence of a homologous series of novel piperidine alkaloids has been detected in the fruits of S. spectabilis by means of tandem mass spectrometry with electrospray ionization. 89 A detailed analysis of the structural features of 70 has led to identification of an acetylcholine (ACh) subunit internalized in this (Figure 17), and led to the design of several semi-synthetic derivatives, including (-)-3-O-acetyl-spectaline hydrochloride (73), prepared from 63. This derivative displays cholinergic activity both in vitro and in vivo (IC 50 = 7.32 μM).…”
Section: Brazilian Biodiversity: An Unknown Potential Source For Drugmentioning
confidence: 99%
“…Also, the authors reported that the extracts obtained from flowers contained more oxygen atoms than those obtained from fruits. On the other hand, the formation of some ions as evidenced in the spectrum of the precursor ion could not be explained on the basis of their ESI-MS/MS data, but they can also be of great importance when this technique is used in combination with NMR (Pivatto et al, 2005). The dereplication of alkaloids has also been achieved by means of UV-Vis spectroscopy in combination with tandem mass spectrometry (MS/MS).…”
Section: Alkaloidsmentioning
confidence: 99%
“…Foi ainda demonstrada a atividade potencialmente antitumoral dos alcaloides − -3-O-acetil-espectalina (11), − -7-hidróxi-espectalina, iso-6-espectalina (3 , − -espectalina (7), obtidos das flores e de frutos verdes de Senna spectabilis, por meio do bioensaio usando linhagens mutantes de Saccharomyces cerevisae com deficiência para atuar no reparo do DNA. 25,26 Figura 2. Estruturas de alcaloides piperidínicos isolados de S. spectabilis Senna spectabilis é a espécie nativa do Brasil que biossintetiza a maior diversidade de alcaloides piperidínicos bioativos, sendo que algumas dessas substâncias apresentaram efeitos farmacológicos de interesse.…”
Section: Alcaloides Piperidínicos Bioativos De Senna Spectabilisunclassified